Comparison of metabolic syndrome prevalence using four different definitions - a population-based study in Finland - Elsi Haverinen; Laura Paalanen; Luigi Palmieri; Alicia Padron-Monedero; Isabel Noguer-Zambrano; Rodrigo Sarmiento Suárez; Hanna Tolonen; for the Joint Action on Health Information (InfAct) (BMC, 2021)
Abstract Background Metabolic syndrome (MetS) is a public health problem in Europe, affecting all age groups. Several MetS definitions are available. The aim of this study was to compare four different MetS definitions in the Finnish adult population, to assess their agreement and to evaluate the impact of the choice of the definition on the prevalence of MetS. Methods Data from FinHealth 2017, a cross-sectional national population health survey, focusing on adults aged 25 years or older were used in the analysis (n=5687). Measured data on anthropometrics, blood pressure and biomarkers together with questionnaire data were used to classify the participants into the MetS categories according to the four definitions. The definitions chosen for the comparison were those by the World Health Organization (WHO) (1998), National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) (2004), International Diabetes Federation (IDF) (2005), and Joint Interim Statement (JIS) (2009). Results The four MetS definitions resulted in substantially different MetS prevalence: 17.7% by WHO, 33.3% by NCEP-ATP III, 41.5% by IDF, and 43.0% by JIS. Regardless of the definition used, the prevalence of MetS increased with age. The prevalence of the different components varied between the definitions, depending on the different cut-off points adopted. Out of all participants, only 13.6% were identified to have MetS according to all four definitions. Agreement between participants recognised by different MetS definitions, estimated through kappa coefficients, was almost perfect for IDF vs. JIS (0.97), strong for JIS vs. NCEP-ATP III (0.80), moderate for IDF vs. NCEP-ATP III (0.76) and weak for WHO vs. NCEP-ATP III (0.42), WHO vs. IDF (0.41) and WHO vs. JIS (0.40). Conclusions Differences between observed prevalence of MetS in Finnish men and women using different MetS definitions were large. For cross-country comparisons, as well as for trend analyses within a country, it is essential to use the same MetS definition to avoid discrepancies in classification due to differences in used definitions.